The growth of the posterior cranial fossa in FGFR2-induced faciocraniosynostosis: A review - Coll, G.; Abed Rabbo, F.; Jecko, V.; Sakka, L.; Di Rocco, F.; Delion, M. (Neuro-chirurgie, 2019)
The growth of the posterior fossa in syndromic craniostenosis was studied in many papers. However, few studies described the pathophysiological growth mechanisms in non-operated infants with fibroblast growth factor receptor (FGFR) type 2 mutation (Crouzon, Apert or Pfeiffer syndrome), although these are essential to understanding cranial vault expansion and hydrocephalus treatment in these syndromes. A review of the medical literature was performed, to understand the physiological and pathological growth mechanisms of the posterior fossa in normal infants and infants with craniostenosis related to FGFR2 mutation. Of the various techniques for measuring posterior fossa volume, direct slice-by-slice contouring is the most precise and sensitive. Posterior fossa growth follows a bi-phasic pattern due to opening of the petro-occipital, occipitomastoidal and spheno-occipital sutures. Some studies reported smaller posterior fossae in syndromic craniostenosis, whereas direct contouring studies reported no difference between normal and craniostenotic patients. In Crouzon syndrome, synchondrosis fusion occurs earlier than in normal subjects, and follows a precise pattern. This premature fusion in Crouzon syndrome leads to a stenotic foramen magnum and facial retrusion.